LIMS configuration to fit new massively parallel sequencing workflows in forensic genetics. (December 2017) - Barrio, Pedro A.; Martin, Pablo; Alonso, Antonio; ,
Abstract: Laboratory Information Management Systems (LIMS) are valuable tools in the forensic genetics laboratory, streamlining sample and analysis traceability, batching of multiple samples, integration and data transfer with genetic analyzers, monitoring of test results, DNA data exchange with National DNA databases, and flexible reporting. This work, developed in the framework of the DNASEQEX project, presents the configuration of a commercial LIMS system to fit the automated workflow provided by the IonChef/Ion S5XL platforms and the Torrent Server Suite/Converge software packages for the massively parallel sequence analysis of STR markers in the forensic lab. LIMS configurations included (1) the setup of analysis and batch templates for DNA library preparation, and DNA library quantification (2) the creation of composite samples for MPS-STR library tracking, (3) the development of files to electronically export MPS sample setups and analysis to the Torrent Server Software, (4) the configuration of scripts for the electronic transfer into the LIMS system of STR allele and sequence data files generated by the Converge software, and (5)the development of DNA data export files to national DNA databases. The developed LIMS configuration provides the laboratory with the tools required for setting up automated MPS workflows, helping to efficiently and accurately acquire, manage, and exchange MPS data in the forensic genetics laboratory.